Bracing the Russell BRACERS: Putting a diverse artifact collection online rapidly - Kemper, David; Lawlor, Debbie; Rzeczkowski, Wiktor (My University, 2016)
BRACERS, the Bertrand Russell Archives Catalogue Entry and Research System, was a mainframe/COBOL era system housing over 126,000 (growing) electronic records from a unique collection of Bertrand Russell's original correspondence, manuscripts of published and unpublished books, essays and articles, photographs and family memorabilia. The collection is owned by the McMaster University Library and physically housed in the William Ready Division of Archives and Research Collections. While bracing the Russell BRACERS for the modern era, we developed a new, scalable, virtual machine-, MariaDB-, Drupal-, and Solr-based deployment environment as well as methods and procedures to put an artifact collection online rapidly and have BRACERS migrated into such an environment.In this presentation we will discuss the deployment environment, issues in putting a new artifact collection into such an environment, and issues in migrating a diverse artifact collection from an antiquated environment into such an environment.
Keywords: artifacts; online; rapidly; collections; open source; legacy; process; project management